Reasons for Joining the Medical Field - Shazia Zeb (Journal of Rawalpindi Medical College, 2014)
Background: To evaluate the reasons for joining the medical field by students of first year MBBS . Methods: This was a descriptive study, carried out in Anatomy Lecture Hall of Rawalpindi Medical College in February 2007. All 205 students of first year MBBS class were enrolled in this study by convenience sampling. Data was collected by means of structured questionnaire. Variables evaluated were age, nationality, sex, board, college and school as well as seat allocation of the students according to merit, scholarship or self-finance. Students were asked about the reasons for joining the medical field, their future ambition and any other family member of same profession. Results: Of the total 205 students of 1st year MBBS class of Rawalpindi Medical College, 59.5% were females while 40.5% were males. 67.8% and 31.7% of the students joined medical field by their own choice and by parents’ choice respectively. Only 0.5% of the students got admission in medical college by luck.35.6% respondents had family members of the same profession. Students who joined medical field by their parents’ choice were found to be more uncertain about their future plans. Female students were found to be less interested in the field of Gynecology /Obstetrics Conclusion: In Pakistan, future selection of children is highly influenced by their parents. Those who join medical field by their parents’ will are found to be uncertain about their future ambition.